Permanent magnetic ferrite as well as preparation method and application thereof
Through heat treatment and dry vibration of ball-grinding ball-grinding iron scales and strontium carbonate pre-firing, combined with the use of appropriate additives, the problems of insufficient reaction and high energy consumption of iron scale raw materials are solved, and the magnetic performance and process efficiency of permanent magnet ferrite are significantly improved. .
Patent Information
- Application Number
- CN202411361023.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, iron scales react sufficiently with solid-phase substances such as strontium carbonate, resulting in low magnetic properties of permanent magnet ferrite, high energy consumption of wet mixing process, and difficult to uniformly mixing through dry process.
The heat-treated iron scales and strontium carbonate dry method are used to vibrate the ball mill, pre-fired, and then mixed with additives to sinter the heat treatment temperature is adjusted to 700-900°C to improve the magnetic properties of the permanent magnet ferrite and simplify the process steps to reduce energy consumption.
The residual magnetism, magnetic inductive coercivity, intrinsic coercivity and maximum magnetic energy product of permanent magnet ferrite are improved, the process steps are simplified, energy consumption is reduced, molar ratio shift is avoided, and magnetic performance is improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic material preparation, and in particular relates to a permanent magnetic ferrite and a preparation method and application thereof. Background Art
[0002] Permanent ferrite is an important permanent magnetic material that can be used in automotive DC motors, starter motors, inductors, audio converters, separators and other fields; therefore, higher requirements are placed on its performance. The main performance indicators are: remanence (Br), magnetic coercivity (Hcb), intrinsic coercivity (Hcj) and maximum magnetic energy product ((BH)max). The performance of permanent ferrite is affected by the performance of its raw material, permanent ferrite. At present, the common method for preparing permanent ferrite is the ceramic oxide method, which is to mix iron oxide (or iron powder), strontium carbonate and rare earth raw materials evenly, put them into a kiln body and sinter them at 1100-1300℃ to obtain permanent ferrite. Therefore, higher requirements are placed on the preparation method of permanent ferrite.
[0003] Iron scale is a common raw material for preparing permanent magnetic ferrite. In the prior art, in order to mix the raw materials evenly, the iron scale is often dried and crushed, and then mixed by a wet or dry process to make the elements fully contact, and additives such as calcium carbonate, silicon dioxide and kaolin are added to improve the performance of the permanent magnetic ferrite; but the lubricating oil, grease, etc. contained in the iron scale will produce a large amount of foam during wet mixing, causing the molar ratio of the mixture to shift. At the same time, the wet mixing needs to be dried again, which requires high energy consumption; and dry mixing is not easy to mix evenly; in addition, the large amount of elemental iron contained in the iron scale will make the iron scale and strontium carbonate insufficient during the solid phase reaction, resulting in generally low magnetic properties of the permanent magnetic ferrite using the iron scale as the raw material. Therefore, it is necessary to provide a preparation method of permanent magnetic ferrite using iron scale as the raw material, which has low energy consumption and high magnetic properties of the obtained permanent magnetic ferrite. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art that iron scale as raw material reacts insufficiently with solid phase materials such as strontium carbonate, the energy consumption is high, and the magnetic properties of the permanent ferrite obtained are low, thereby providing a permanent ferrite and its preparation method and application.
[0005] To this end, the present invention provides the following technical solutions.
[0006] The present invention provides a method for preparing a permanent magnetic ferrite, comprising the following steps:
[0007] (1) mixing the heat-treated iron scale with strontium carbonate, dry-vibrating ball milling, and pre-calcining to obtain a pre-calcined powder; wherein the heat treatment temperature is 700-900° C.;
[0008] (2) The pre-fired powder is mixed with a first additive and sintered.
[0009] The permanent magnet ferrite prepared by the preparation method of the permanent magnet ferrite provided by the present invention has good performance, and its remanence (Br), magnetic coercivity (Hcb), intrinsic coercivity (Hcj) and maximum magnetic energy product ((BH)max) are relatively high; specifically, after the iron scale is heat-treated and mixed with strontium carbonate, a solid phase reaction is more likely to occur, thereby improving the remanence (Br), magnetic coercivity (Hcb), intrinsic coercivity (Hcj) and maximum magnetic energy product ((BH)max) of the prepared permanent magnet ferrite. At the same time, step (1) adopts a vibration ball milling method to mix the crushed iron scale and the mixed raw materials in one step, and no drying is required, which effectively reduces energy consumption. Compared with the method of crushing first and then mixing in the prior art, the method of the present invention significantly simplifies the process steps and ensures mixing uniformity; compared with the wet mixing process in the prior art, the present invention does not have a large molar deviation.
[0010] As an example, the heat treatment temperature may be 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C or a range formed by any two of the above values.
[0011] In an optional embodiment, based on the mass of the pre-sintered powder, the amount of the first additive does not exceed 3wt%;
[0012] Preferably, the first additive comprises at least one of silicon dioxide and calcium carbonate;
[0013] Preferably, the amount of silicon dioxide is 0.1-0.6wt% based on the mass of the pre-calcined powder;
[0014] Preferably, the amount of calcium carbonate is 0.5-1.5wt% based on the mass of the pre-burnt powder;
[0015] Preferably, the mass ratio of the silicon dioxide to the calcium carbonate is 1:(2-4).
[0016] As an example, the amount of silicon dioxide in the first additive can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt% or in the range formed by any two of the above values; the amount of calcium carbonate can be 0.5wt%, 0.7wt%, 1.0wt%, 1.3wt%, 1.5wt% or in the range formed by any two of the above values.
[0017] It should be noted that the total amount of silicon dioxide and / or calcium carbonate added does not exceed 3 wt % of the mass of the pre-calcined powder, and is preferably 0.6-2.1 wt %.
[0018] In an optional embodiment, the first additive further comprises at least one of lanthanum oxide, cobalt oxide, aluminum oxide, and strontium carbonate;
[0019] In an optional embodiment, the amount of lanthanum oxide does not exceed 1.5wt% based on the mass of the pre-sintered powder;
[0020] In an optional embodiment, the amount of the cobalt oxide does not exceed 0.5wt% based on the mass of the pre-sintered powder;
[0021] In an optional embodiment, the amount of strontium carbonate does not exceed 0.5wt% based on the mass of the pre-burnt powder;
[0022] In an optional embodiment, the amount of alumina does not exceed 0.5wt% based on the mass of the pre-burnt powder;
[0023] In an optional embodiment, the mass ratio of cobalt oxide to lanthanum oxide is 1:(2-3).
[0024] In an optional embodiment, the first additive includes silicon dioxide and calcium carbonate, and also includes at least one of lanthanum oxide, cobalt oxide, aluminum oxide, and strontium carbonate; when the first additive also includes at least one of lanthanum oxide, cobalt oxide, aluminum oxide, and strontium carbonate, based on the mass of the pre-burned powder, the amount of lanthanum oxide does not exceed 1.5wt%, the amount of cobalt oxide does not exceed 0.5wt%, the amount of strontium carbonate does not exceed 0.5wt%, and the amount of aluminum oxide does not exceed 0.5wt%; the total amount of each component added in the first additive does not exceed 3wt% of the mass of the pre-burned powder.
[0025] In an optional embodiment, the heat treatment time is not less than 0.5h.
[0026] In an optional embodiment, the heat treatment time is 0.5-2h.
[0027] The present invention regulates the heat treatment temperature to 700-900°C and the time to be not less than 0.5h, which can reduce the residual ferrous oxide and elemental iron in the iron scale and ensure that the iron scale and strontium carbonate solid phase reaction are complete. The heat treatment time is not more than 2h, and the heat treatment can be completed within a relatively suitable time without causing energy waste.
[0028] In an optional embodiment, in the step (1), the mixing further comprises adding at least one of silicon dioxide and aluminum oxide.
[0029] In the present invention, adding alumina or silicon dioxide in step (1) can further improve the remanence, magnetic coercivity, intrinsic coercivity and maximum magnetic energy product of the permanent ferrite.
[0030] In an optional embodiment, the molar ratio of the iron element in the iron scale to the strontium element in strontium carbonate is (11.6-12.4):1; as an example, the molar ratio of the iron element in the iron scale to the strontium element in strontium carbonate is 11.6:1, 11.8:1, 12:1, 12.3:1 or within the range of any two of the above ratios.
[0031] In an optional embodiment, based on the total mass of the strontium carbonate and the iron scale, the mass addition amount of the silicon dioxide is 0-0.3wt%;
[0032] In an optional embodiment, based on the total mass of the strontium carbonate and the iron scale, the mass addition amount of the aluminum oxide is 0-0.3 wt %.
[0033] It should be noted that the mass addition amount of silicon dioxide being 0 means that silicon dioxide is not added during mixing; and the mass addition amount of aluminum oxide being 0 means that aluminum oxide is not added during mixing.
[0034] In an optional embodiment, in step (1), the mixing time is 5-10 min;
[0035] In an optional embodiment, the particle size of the powder after dry vibration ball milling is 2-4 μm.
[0036] In an optional embodiment, the pre-burning temperature is 1250-1300°C;
[0037] In an optional embodiment, the pre-burning time is 1-3h;
[0038] As an example, the pre-firing temperature of the present invention can be 1250°C, 1260°C, 1270°C, 1280°C, 1290°C, 1300°C or within the range formed by any two of the above values; the pre-firing time can be 1h, 1.5h, 2h, 2.5h, 3h or within the range formed by any two of the above values.
[0039] In an optional embodiment, in step (2), the particle size of the pre-calcined powder is 4-6 μm;
[0040] The present invention adjusts the particle size of the pre-burned powder to 4-6 μm, and the raw materials can be mixed evenly; it can be understood that after obtaining the pre-burned powder in step (1), the step of crushing it to a particle size of 4-6 μm is included, and then the crushed pre-burned powder is mixed with the first additive.
[0041] In the step (2), the mixing is performed by ball milling or the like, and the mixing time is 6-12 hours;
[0042] After the mixing, a slurry is obtained, and the particle size of the slurry is 0.8-1 μm;
[0043] The step (2), after the mixing, further comprises wet pressing in a magnetic field;
[0044] In an optional embodiment, the sintering temperature is 1230-1250°C;
[0045] In an optional embodiment, the sintering time is 0.5-1.5h.
[0046] As an example, the sintering temperature of the present invention can be 1230°C, 1235°C, 1240°C, 1243°C, 1247°C, 1250°C or within the range formed by any two of the above values; the sintering time can be 0.5h, 0.7h, 0.9h, 1.2h, 1.5h or within the range formed by any two of the above values.
[0047] The present invention provides a permanent ferrite prepared by the preparation method.
[0048] The present invention provides an application of the permanent ferrite prepared by the preparation method in magnetic materials.
[0049] The technical solution of the present invention has the following advantages:
[0050] 1. The preparation method of the permanent magnet ferrite provided by the present invention comprises: (1) heat treating iron scale, first mixing, and pre-sintering to obtain pre-sintered powder; (2) second mixing the pre-sintered powder with a second additive, and sintering to obtain the permanent magnet ferrite. The permanent magnet ferrite prepared by the present invention has high remanence (Br), magnetic induction coercive force (Hcb), intrinsic coercive force (Hcj) and maximum magnetic energy product ((BH)max); specifically, the present invention heat-treats the iron scale so that the ferrous oxide and elemental iron therein are oxidized into ferric oxide, which is more likely to react with strontium carbonate in a solid phase, so that the remanence (Br), magnetic induction coercive force (Hcb), intrinsic coercive force (Hcj) and maximum magnetic energy product ((BH)max) of the prepared permanent magnet ferrite are high; the mixing in step (1) of the present invention combines the two steps of crushing the iron scale and mixing the raw materials in the prior art into one step, simplifies the process and effectively reduces energy consumption; at the same time, the mixing in step (1) is dry mixing, which does not need to be dried again, and can effectively reduce energy consumption and save costs. The present invention adds the first additive for mixing, and the magnetic properties of the permanent magnet ferrite can be improved through the synergistic effect between the additives.
[0051] 2. The preparation method of the permanent magnet ferrite provided by the present invention can make the remanence, magnetic coercivity, intrinsic coercivity and maximum magnetic energy product of the permanent magnet ferrite higher by adding alumina or silicon dioxide; the heat treatment temperature is 700-900°C. If the temperature is too low or the heat treatment time is less than 0.5h, more ferrous oxide and elemental iron will remain in the iron scale and cannot react completely with strontium carbonate in the solid phase, resulting in low performance of the permanent magnet ferrite; if the temperature is too high or the heat treatment time is more than 2h, it will cause energy waste. DETAILED DESCRIPTION
[0052] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0053] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0054] In the prior art, permanent magnet ferrite is often prepared by mixing iron scale and strontium carbonate, wet grinding, adding additives and mixing before sintering. However, lubricating oil, grease, etc. contained in the iron scale will produce a large amount of foam during wet mixing, causing the molar ratio of the mixture to shift. At the same time, after wet mixing, it needs to be dried again, which requires high energy consumption. In addition, the elemental iron that accounts for a large proportion of the iron scale is not easy to react with strontium carbonate in the solid phase, and the performance of the permanent magnet ferrite obtained is relatively low.
[0055] In order to solve the problems existing in the above-mentioned related technologies, the present invention provides the following technical solutions:
[0056] According to a first aspect of the present invention, the present invention provides a method for preparing a permanent ferrite, comprising the following steps:
[0057] After heat treatment of the iron scale, strontium carbonate is added, dry vibration ball milling is performed, and pre-calcination is performed to obtain pre-calcined powder;
[0058] The pre-sintered powder is crushed, mixed with the first additive by ball milling, and then wet pressed in a magnetic field and sintered to obtain a permanent ferrite.
[0059] It should be noted that the amount of water added is a well-known amount in the art and is not specifically limited, as long as molding is ensured.
[0060] In the present invention, the addition of the first additive can effectively improve the remanence (Br), magnetic coercivity (Hcb), intrinsic coercivity (Hcj) and maximum magnetic energy product ((BH)max) of the prepared permanent ferrite, wherein the first additive includes silicon dioxide and calcium carbonate; the first additive also includes at least one of lanthanum oxide, cobalt oxide, aluminum oxide and strontium carbonate;
[0061] In a second aspect, the present invention also provides a permanent ferrite prepared by the above preparation method.
[0062] In a third aspect, the present invention also provides an application of the permanent ferrite prepared by the above preparation method in magnetic materials.
[0063] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.
[0064] Example 1
[0065] This embodiment provides a method for preparing a permanent magnetic ferrite, comprising the following steps:
[0066] (1) The Baosteel steel scale was heat treated at 800°C for 1 hour in a tempering kiln, red disc strontium carbonate and silicon dioxide were added, and the mixture was mixed by vibration ball milling for 10 minutes to obtain a precursor powder, wherein the particle size of the precursor powder was 2 μm; wherein the molar ratio of the iron element in the Baosteel steel scale to the strontium element in the red disc strontium carbonate was 12.1:1, and the amount of silicon dioxide added was 0.2 wt% based on the total mass of the Baosteel steel scale and the red disc strontium carbonate; and the mixture was pre-fired at 1280°C for 1 hour in a pre-fired furnace to obtain a pre-fired powder;
[0067] (2) The pre-burned powder is crushed to a particle size of 5 μm, silicon dioxide and calcium carbonate are added and ball-milled for 10 hours, mixed with water to obtain a slurry, and then wet-pressed in a magnetic field to form the slurry, wherein the particle size of the slurry is 0.9 μm; based on the mass of the pre-burned powder, the mass amount of silicon dioxide added is 0.2wt%, and the mass amount of calcium carbonate added is 0.8wt%; it is sintered at 1230°C for 1 hour to obtain a permanent magnet ferrite.
[0068] Example 2
[0069] This embodiment provides a method for preparing permanent magnetic ferrite, which is different from the embodiment 1 in that the sintering temperature is 1250° C. instead of 1230° C. in the embodiment 1.
[0070] Example 3
[0071] This embodiment provides a method for preparing a permanent magnetic ferrite, comprising the following steps:
[0072] (1) The Baosteel scale was heat treated at 900°C in a tempering kiln for 0.5h, red disc strontium carbonate and silicon dioxide were added, and the mixture was vibrated and ball milled for 5min to obtain a precursor powder, wherein the particle size of the precursor powder was 4μm; wherein the molar ratio of the iron element in the Baosteel scale to the strontium element in the red disc strontium carbonate was 12.4:1, and the mass addition amount of the silicon dioxide was 0.3wt% based on the total mass of the Baosteel scale and the red disc strontium carbonate; and the mixture was pre-fired at 1300°C in a pre-fired furnace for 1h to obtain a pre-fired powder;
[0073] (2) The pre-burned powder is crushed to a particle size of 6 μm, and silicon dioxide, calcium carbonate and strontium carbonate are added and ball-milled for 6 hours. The mixture is mixed with water to obtain a slurry, and then wet-pressed in a magnetic field to form the slurry, wherein the particle size of the slurry is 1.0 μm. Based on the mass of the pre-burned powder, the mass amount of silicon dioxide added is 0.3wt%, the mass amount of calcium carbonate added is 0.8wt%, and the mass amount of strontium carbonate added is 0.4wt%; the sintered powder is sintered at 1230°C for 1 hour to obtain a permanent magnet ferrite.
[0074] Example 4
[0075] This embodiment provides a method for preparing permanent magnetic ferrite, which is different from the embodiment 3 in that the sintering temperature is 1250° C. instead of 1230° C. in the embodiment 3.
[0076] Example 5
[0077] This embodiment provides a method for preparing a permanent magnetic ferrite, comprising the following steps:
[0078] (1) The Baosteel scale was heat treated at 700°C for 2 hours in a tempering kiln, red disc strontium carbonate was added, and the mixture was vibrated and ball milled for 7 minutes to obtain a precursor powder, wherein the particle size of the precursor powder was 3 μm; wherein the molar ratio of the iron element in the Baosteel scale to the strontium element in the red disc strontium carbonate was 11.9:1; and the mixture was pre-calcined at 1250°C for 3 hours in a pre-calcining furnace to obtain a pre-calcined powder;
[0079] (2) The pre-burned powder is crushed to a particle size of 4 μm, and silicon dioxide and calcium carbonate are added to the powder and ball-milled for 12 hours. The powder is mixed with water to obtain a slurry, and then wet-pressed in a magnetic field to form the slurry, wherein the particle size of the slurry is 0.8 μm. Based on the mass of the pre-burned powder, the mass amount of silicon dioxide added is 0.3 wt%, and the mass amount of calcium carbonate added is 1.0 wt%. The powder is sintered at 1230° C. for 1 hour to obtain a permanent ferrite.
[0080] Example 6
[0081] This embodiment provides a method for preparing permanent magnetic ferrite, which is different from the embodiment 5 in that the sintering temperature is 1250° C. instead of 1230° C. in the embodiment 5.
[0082] Example 7
[0083] This embodiment provides a method for preparing a permanent magnetic ferrite, comprising the following steps:
[0084] (1) The Baosteel scale was heat treated at 800°C for 1 hour in a tempering kiln, red disc strontium carbonate was added, and the mixture was vibrated and ball milled for 8 minutes to obtain a precursor powder, wherein the particle size of the precursor powder was 2.6 μm; wherein the molar ratio of the iron element in the Baosteel scale to the strontium element in the red disc strontium carbonate was 12.3:1; and the mixture was pre-calcined at 1270°C for 1.5 hours in a pre-calcining furnace to obtain a pre-calcined powder;
[0085] (2) The pre-calcined powder is crushed to a particle size of 5.5 μm, and silicon dioxide, calcium carbonate, lanthanum oxide and cobalt oxide are added and ball-milled for 10 hours. The mixture is mixed with water to obtain a slurry, and then wet-pressed in a magnetic field to form the slurry, wherein the particle size of the slurry is 0.86 μm. Based on the mass of the pre-calcined powder, the mass amount of silicon dioxide added is 0.3wt%, the mass amount of calcium carbonate added is 1.0wt%, the mass amount of lanthanum oxide added is 0.4wt%, and the mass amount of cobalt oxide added is 0.2wt%. The powder is sintered at 1230°C for 1 hour to obtain a permanent magnet ferrite.
[0086] Example 8
[0087] This embodiment provides a method for preparing permanent magnetic ferrite, which is different from Embodiment 7 in that the sintering temperature is 1250° C. instead of 1230° C. in Embodiment 7.
[0088] Comparative Example 1
[0089] This comparative example provides a method for preparing a permanent magnetic ferrite, comprising the following steps:
[0090] (1) mixing Baosteel scale, red disc strontium carbonate and water, mixing by vibration ball milling for 10 minutes, and drying in an oven; wherein the molar ratio of the iron element in the Baosteel scale to the strontium element in the red disc strontium carbonate is 12.3:1; pre-calcining in a pre-calcining furnace at 1280° C. for 1 hour to obtain a pre-calcined powder;
[0091] (2) The pre-burned powder is crushed to a particle size of 6.5 μm, and silicon dioxide and calcium carbonate are added and ball-milled for 10 hours to obtain a slurry, which is then wet-pressed in a magnetic field and molded. The particle size of the slurry is 0.85 μm. Based on the mass of the pre-burned powder, the mass of silicon dioxide is 0.3 wt%, and the mass of calcium carbonate is 1.0 wt%. The slurry is sintered at 1230° C. for 1 hour to obtain a permanent ferrite.
[0092] Test example
[0093] This test example provides permanent magnetic ferrites prepared in various embodiments and comparative examples. The magnetic properties thereof are measured by a BH tester, and the molar ratio M of the iron and strontium elements in the permanent magnetic ferrites is analyzed by fluorescence, as follows:
[0094] Table 1 Performance test results of various embodiments and comparative examples
[0095] Br(Gs) Hcb(Oe) Hcj(Oe) (BH)max(MGOe) M Example 1 4071 3156 3188 4.079 12.14 Example 2 4093 3098 3100 4.138 12.08 Example 3 4074 3189 3375 4.105 12.34 Example 4 4096 3107 3298 4.210 12.36 Example 5 4072 3250 3378 4.149 11.86 Example 6 4093 3190 3299 4.221 11.9 Example 7 4102 3350 3578 4.249 12.3 Example 8 4123 3290 3499 4.321 12.26 Comparative Example 1 4008 3045 3121 4.078 12.8
[0096] It can be seen from the above results that the permanent ferrite prepared by the present invention has relatively high remanence, magnetic induction coercive force, intrinsic coercive force and maximum magnetic energy product.
[0097] It can be seen from Examples 7-8 that the addition of cobalt oxide and lanthanum oxide as the first additive can effectively improve the performance of the permanent magnet ferrite obtained, but the price of cobalt oxide is relatively high, and the cost performance needs to be comprehensively considered.
[0098] Example 7 is compared with Comparative Example 1. In Comparative Example 1, iron scale, strontium carbonate and water are mixed. The iron scale is not heat-treated. The lubricating oil, grease, etc. contained therein will produce a large amount of foam during wet mixing, so that the molar ratio of Baosteel iron scale and red disc strontium carbonate shifts from 12.3:1 to 12.8:1. The remanence, magnetic coercive force, intrinsic coercive force and maximum magnetic energy product of the permanent magnet ferrite obtained are significantly reduced.
[0099] The method for preparing permanent ferrite provided by the present invention simplifies the prior art. In the prior art, iron scale and strontium carbonate are often wet-milled with water to allow each element to fully contact, but they need to be dried again before pre-burning to obtain permanent ferrite. The present invention uses dry mixing, which does not require drying again and can save energy.
[0100] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a permanent magnetic ferrite, characterized in that: The steps include: (1) mixing the heat-treated iron scale with strontium carbonate, dry-vibrating ball milling, and pre-calcining to obtain a pre-calcined powder; wherein the heat treatment temperature is 700-900° C.; (2) The pre-fired powder is mixed with a first additive and sintered.
2. The preparation method according to claim 1, characterized in that: Based on the mass of the pre-sintered powder, the amount of the first additive does not exceed 3wt%; Preferably, the first additive comprises at least one of silicon dioxide and calcium carbonate; Preferably, the amount of silicon dioxide is 0.1-0.6wt% based on the mass of the pre-calcined powder; Preferably, the amount of calcium carbonate is 0.5-1.5wt% based on the mass of the pre-burnt powder; Preferably, the mass ratio of the silicon dioxide to the calcium carbonate is 1:(2-4).
3. The preparation method according to claim 2, characterized in that: The first additive also includes at least one of lanthanum oxide, cobalt oxide, aluminum oxide, and strontium carbonate; Preferably, the amount of lanthanum oxide used is no more than 1.5wt% based on the mass of the pre-sintered powder; Preferably, based on the mass of the pre-sintered powder, the amount of the cobalt oxide does not exceed 0.5wt%; Preferably, the amount of strontium carbonate does not exceed 0.5wt% based on the mass of the pre-burnt powder; Preferably, the amount of alumina does not exceed 0.5wt% based on the mass of the pre-burnt powder; Preferably, the mass ratio of cobalt oxide to lanthanum oxide is 1:(2-3).
4. The preparation method according to any one of claims 1 to 3, characterized in that: The heat treatment time is 0.5-2h.
5. The preparation method according to claim 1, characterized in that: In the step (1), the mixing further comprises adding at least one of silicon dioxide and aluminum oxide.
6. The preparation method according to claim 5, characterized in that: The molar ratio of the iron element in the iron scale to the strontium element in the strontium carbonate is (11.6-12.4):1; and / or, Based on the total mass of the strontium carbonate and the iron scale, the mass addition amount of the silicon dioxide is 0-0.3wt%; and / or, Based on the total mass of the strontium carbonate and the iron scale, the mass addition amount of the aluminum oxide is 0-0.3wt%.
7. The preparation method according to claim 1, characterized in that: In step (1), the mixing time is 5-10 min; and / or, The particle size of the powder after dry vibration ball milling is 2-4 μm; and / or, The pre-firing temperature is 1250-1300° C.; and / or, The pre-burning time is 1-3h.
8. The preparation method according to claim 1, characterized in that: In step (2), the particle size of the pre-calcined powder is 4-6 μm; and / or, The sintering temperature is 1230-1250° C.; and / or, The sintering time is 0.5-1.5h.
9. The permanent ferrite obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the permanent ferrite prepared by the preparation method according to any one of claims 1 to 8 in magnetic materials.
Citation Information
Cited By
Preparation process of high-resistance M-type hexagonal ferrite and prepared product
CN119751041A
Preparation process of high-resistance M-type hexaferrite and product prepared thereby
CN119751041B
